2020
DOI: 10.1128/jcm.00981-19
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Commercial Tools for Metagenomic Shotgun Sequencing Analysis

Abstract: Metagenomic shotgun sequencing for the identification of pathogens is being increasingly utilized as a diagnostic method. Interpretation of large and complicated data sets is a significant challenge, for which multiple commercial tools have been developed. Three commercial metagenomic shotgun sequencing tools, CosmosID, One Codex, and IDbyDNA, were compared to determine whether they result in similar interpretations of the same sequencing data. We selected 24 diverse samples from a previously characterized dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The results observed from real-world applications have difficulty reaching the level claimed by method validation because they are easily affected by various variation factors associated with samples, laboratory environment, reagents, consumables and human operation [7] . Increasing studies have made efforts to enhance the detection sensitivity of mNGS for different specimen types by optimizing the procedures of sample preparation [17] , nucleic acid extraction and purification [33] , library preparation [34] , sequencing amount/depth [35] and bioinformatics tools [20] , [21] , [36] . The interference of host DNA in clinical samples and the different efficiency of nucleic acid extraction kits to different microbial DNA are considered to be two critical obstacles that affect the sequencing results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results observed from real-world applications have difficulty reaching the level claimed by method validation because they are easily affected by various variation factors associated with samples, laboratory environment, reagents, consumables and human operation [7] . Increasing studies have made efforts to enhance the detection sensitivity of mNGS for different specimen types by optimizing the procedures of sample preparation [17] , nucleic acid extraction and purification [33] , library preparation [34] , sequencing amount/depth [35] and bioinformatics tools [20] , [21] , [36] . The interference of host DNA in clinical samples and the different efficiency of nucleic acid extraction kits to different microbial DNA are considered to be two critical obstacles that affect the sequencing results.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratories adopt highly customized strategies based on their own experiences for reducing inter-sample/laboratory/reagent contamination, removing host DNA interference, improving the efficiency of microbial nucleic acid extraction methods, increasing the integrity of the reference database and enhancing the accuracy of bioinformatics algorithms [17] , [18] . These nonstandardized processing strategies greatly affect the interlaboratory reproducibility of metagenomic sequencing, leading to uncertainty in the results [19] , [20] , [21] . As reported, the sensitivity and specificity of mNGS platforms developed in different laboratories for diagnosing infectious disease vary widely, ranging from 50.7% to 96.6% and 41.7% to 85.7%, respectively [10] , [22] , [23] .…”
Section: Introductionmentioning
confidence: 99%
“…Fecal specimens were collected before euthanasia and submitted to CosmosID for whole-genome shotgun sequencing as detailed elsewhere (51,52). Comparative taxonomic analysis was performed using the CosmosID-HUB bioinformatics platform (53)(54)(55). No differences in alpha diversity (Chao1, Shannon and Simpson indices) (fig.…”
Section: (S)-ibd3540 Is Efficacious In Established Spontaneous Chroni...mentioning
confidence: 99%
“…The copyright holder for this this version posted December 30, 2022. ; https://doi.org/10.1101/2022.12.28.22284010 doi: medRxiv preprint Multi-omics approaches have recently been investigated as potential alternatives to overcome limitations of currently used diagnostic tools [26,29,[37][38][39][40] . Previous studies have shown that liquid chromatography-tandem mass spectrometry (LC-MS/MS)-based profiling may be able to differentiate synovial fluid samples from PJI and NIAF patients [31,41] .…”
Section: Introductionmentioning
confidence: 99%